QUALITATIVE APPROACH IN LAW ENFORCEMENT ANALYSIS: A STUDY OF CHALLENGES AND PRACTICES IN INDONESIA - Wulandari, Septi; Nur Azizah, Dina; Rohmat, Faizal (Jurnal Multidisipliner Bharasa, 2026)
This research aims to analyze law enforcement through a qualitative approach with an emphasis on an in-depth understanding of the challenges and practices that occur in the social, cultural, and institutional context in Indonesia. The qualitative approach was chosen because it allows researchers to explore the experiences, perceptions, and interpretations of law enforcement actors and society comprehensively. So far, law enforcement studies tend to be dominated by normative and quantitative approaches that focus more on regulatory and statistical aspects. In fact, the dynamics of legal practice in the field are often influenced by non-juridical factors such as legal culture, power structure, and socioeconomic conditions of the community. Therefore, this study seeks to fill this gap by providing a more contextual and reflective analysis. This study uses in-depth interviews, observations, and documentation studies on law enforcement practices in several institutions and communities that interact directly with the legal system. The results of the study show that the challenges of law enforcement are not only related to regulatory limitations, but also include the integrity of the apparatus, professionalism, access to justice, and public trust. In addition, it was found that law enforcement practices are often influenced by certain power and interest relationships, thus potentially causing injustice. On the other hand, there are also good practices that show a commitment to substantive justice. The findings of this research are expected to contribute to the development of law enforcement theories and practices that are more responsive to the needs of the community. This research also emphasizes the importance of reforming the legal system that is not only structural, but also cultural. Thus, a qualitative approach can be a strategic alternative in understanding the complexity of law enforcement in more depth.